Information on mini-livestock - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The Bureau for Exchange and Distribution of Information on Mini-Livestock (BEDIM). with financial assistance from CTA, produces a twice-yearly bulletin on information on mini-livestock. In the current issue (Volume 3, No. 1, 1994) the editor states...